An Introduction to n-th Order Limit Language - Siti Hajar, Mohd Khairuddin; Muhammad Azrin, Ahmad; Noraziah, Adzhar (International Association of Engineers, 2022)
The study of the splicing system swiftly grew after Tom Head investigated the biochemical process modelling involving the DNA in 1987. The process of the splicing system consists of a cut and paste of the DNA molecules. Splicing language produced by the splicing system can be classified into inert, transient, and limit language. Previously, second-order limit language was described as a new set of language from the previous splicing language. In this research, we would like to extend the study to n-th order limit language by investigating the effect of the number of rules involved in the splicing system. Following from here, its properties are explored using the formal language theory.